2018
DOI: 10.3390/toxics6030047
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Methylmercury-Induced Cell Toxicity

Abstract: Methylmercury (MeHg) is a hazardous environmental pollutant, which elicits significant toxicity in humans. The accumulation of MeHg through the daily consumption of large predatory fish poses potential health risks, and the central nervous system (CNS) is the primary target of toxicity. Despite well-described neurobehavioral effects (i.e., motor impairment), the mechanisms of MeHg-induced toxicity are not completely understood. However, several lines of evidence point out the oxidative stress as an important m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 141 publications
0
31
0
1
Order By: Relevance
“…Several reports have suggested that calcium dyshomeostasis 44,45 , oxidative stress 46,47 , and disruption of the cytoskeleton 48 are important mechanisms accounting for MeHg-induced neurotoxicity. How do these mechanistic signals regulate JNK-activated autophagy induction?…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that calcium dyshomeostasis 44,45 , oxidative stress 46,47 , and disruption of the cytoskeleton 48 are important mechanisms accounting for MeHg-induced neurotoxicity. How do these mechanistic signals regulate JNK-activated autophagy induction?…”
Section: Discussionmentioning
confidence: 99%
“…Environmental triggers, such as exposure to cigarette smoke, UV radiation, heavy metal ions, ozone, allergens, drugs or toxins, pollutants, pesticides, or insecticides, may all contribute to the increase of ROS production in cells (Antunes dos Santos et al, 2018;Mahajan et al, 2018;Oke et al, 2019).…”
Section: Exogenous Rosmentioning
confidence: 99%
“…Subsequently, NRF2 translocates into the nucleus and binds to the antioxidant response element (ARE) located within the promoter region of specific target genes, inducing the expression of a large number of cytoprotective proteins with antioxidant and detoxifying roles [2][3][4][5]. The importance of NRF2 function has been demonstrated by several studies using NRF2-deficient mice showing an increased susceptibility to redox disturbances and xenobiotic stress [6][7][8]. It has also been shown that tissue oxidative damage after ischemia and reperfusion is efficiently counteracted by NRF2 induction [9].…”
Section: Introductionmentioning
confidence: 99%